Perencanaan Kawasan Sponge City Berdasarkan Prinsip-Prinsip Water Sensitive Urban Design (WSUD) - Ramdan Pano; Arifuddin Akil; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
In less than 6 months, the city of Makassar experienced various urban water problems. In the period August to October 2018 experienced a water crisis due to the impact of the prolonged dry season. As a result, the northern and southern regions of the city underwent a decrease in clean water supply. While entering the period November - January, the intensity of rainfall is very high causing floods that wiped out the entire in this areas. The purpose of this thesis is to plan and to design a sponge city area that is able to support the water resilience city with a case study in Tamanlanrea District. The Sponge City area refers to an area that not only absorbs water, but also advanced stage water treatment which consists of infiltration, treatment, and reuse. In this plan, the author uses the concept of Water Sensitive Urban Design (WSUD) to realize the area of ​​Sponge City in Tamalanrea District. The basic principles of WSUD are zero runoff, eco-drainage, and 5R + with a program of reducing, reusing, recycling, recovering and recharging. Data collection methods obtained from primary data consisting of observation and interviews, as well as secondary datum consisting of topographic, rainfall, previous flood maps, drainage networks, watershed, etc. The analysis methods in this planning are ArcGIS analysis by overlaying and scoring the spatial data obtained from secondary data and descriptive analysis to determine the technical planning and design of the site using Sketch-Up application. The results of this planning are sponge city design with the principles and technical guidelines for implementing the WSUD concept.